2019
DOI: 10.1186/s13567-019-0624-4
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae mannan induces sheep beta-defensin-1 expression via Dectin-2-Syk-p38 pathways in ovine ruminal epithelial cells

Abstract: The rumen epithelium of sheep serves as an immune interface with the environment and secretes antimicrobial peptides with bactericidal function against various pathogens. Sheep beta-defensin-1 (SBD-1), an antimicrobial peptide, is secreted from ovine ruminal epithelial cells (OREC) in response to microbial infections. Mannan, the main component of the Saccharomyces cerevisiae cell wall can stimulate innate and regulatory immune responses that could improve the gastrointestinal environment. We aimed at investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The expression levels of tumor necrosis factor- α (TNF- α ), interferon-gamma (IFN- γ ), interleukin (IL) 4, and IL-5 in plasma were determined by ELISA as per the ELISA kit instructions (MILLIPLEX multifactor detection kit, Merck Biotechnology Co., Ltd., Germany). A microplate reader was used to measure the OD value at 450 nm (1510, Thermo, USA), and the concentration was calculated by a standard curve [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The expression levels of tumor necrosis factor- α (TNF- α ), interferon-gamma (IFN- γ ), interleukin (IL) 4, and IL-5 in plasma were determined by ELISA as per the ELISA kit instructions (MILLIPLEX multifactor detection kit, Merck Biotechnology Co., Ltd., Germany). A microplate reader was used to measure the OD value at 450 nm (1510, Thermo, USA), and the concentration was calculated by a standard curve [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…This structure is distinct from other plant cell wall mannans, such as konjac glucomannan and carob galactomannan, which include only β-linked mannose and not α-linked mannose 3 . YM has various effects in cells and mouse models, including immunomodulation, wound repair, and anti-inflammatory effects, and has potential health benefits in humans and animals 4 6 . YM appears to be utilised by specific intestinal bacteria due to its elaborate structure 7 , and the impacts of YM on the intestinal microbiota ecosystem have attracted research attention.…”
Section: Introductionmentioning
confidence: 99%
“…According to Ackermann et al [ 27 ], the decreased sheep β-defensin-1 expression observed during acute Mannheimia haemolytica pneumonia is in stark contrast to the enhanced sheep β-defensin-1 expression shown during parainfluenza virus type 3 (PI-3) infection. According to Jin et al [ 28 ], Saccharomyces cerevisiae mannan induces sheep β-defensin-1 in a concentration- and time-dependent way and that the effect is diminished when the mannan concentration is too low or too high.…”
Section: Resultsmentioning
confidence: 99%